Assisted praying mat for Muslim / Muhammad Mujahid Mohd Rosli - Mohd Rosli, Muhammad Mujahid (2024)
Muslims can use the Smart Prayer Mat with Rakaat Counter, an innovative idea created to help them with daily prayers. Islam places great emphasis on prayer, yet it can be difficult for certain people to correctly count their rakaat (prayer cycles). The goal of this endeavor is to offer a cutting-edge technical solution that enriches and simplifies the prayer experience. The Rakaat Counter and Qibla Compass included in the Smart Prayer Mat make manual counting and perfect alignment unnecessary. The Rakaat Counter correctly counts the number of rakaat done by using ultrasonic sensors and cutting-edge algorithms to detect prostrations. Throughout the prayer session, users are guided by visual and audible feedback, which encourages accuracy and attention. With its intuitive design, the Smart Prayer Mat appeals to people of all ages and religious backgrounds. It minimizes disruptions during prayer, allowing for a deeper and spiritually rewarding experience. It does this by automating counting and alignment. In conclusion, the Smart Prayer Mat with Rakaat Counter makes use of technology to simplify and strengthen Muslims' adherence to their religion during daily prayers.